MENGIMPLEMENTASIKAN TOTAL QUALITI MANAGEMENT DALAM PENDIDIKAN AGAMA ISLAM - Ahmad Syaifulloh (Jurnal Studi Islam dan Sosial, 2019)
The concept of Total Quality Management (TQM) that has been sparked by Deming, Juran and Crosby initially aimed to overcome several problems in the business and industrial fields, especially in improving quality quality. The concept has been implemented very successfully by the business and industrial world in Japan, and other countries in the world. And then TQM began to be adopted in the world of education around 1980. Implementation of TQM in the world of education has been widely carried out in Indonesia today, and experts have discussed it a lot in their books. However, most are only for education in general, in the sense that there is very little or even no one has discussed the implementation of TQM in Islamic religious education specifically. Considering the current religious education is a priority in order to instill moral values in generations in Indonesia. So it is very necessary to find ways how to improve the quality of quality in religious education, especially Islam. TQM is a management system that involves all components of the organization that are carried out continuously to produce quality products / services in accordance with customer needs and oriented to customer satisfaction. Based on several definitions of TQM above, there are at least four concepts in TQM, including: Quality / Quality, customer satisfaction, continuous improvement, involving all components of the organization. The steps for implementing TQM in Islamic Religious Education are as follows: a). Leadership and commitment to quality must come from the top. b). Delighting customers is the goal of TQM. c). Appoint quality facilitators. d) Form a quality control group. e) Appoint a quality coordinator. f). Hold a senior management seminar to evaluate the program. g). Analyze and diagnose the situation. h). Use examples that have already developed elsewhere. i). Hire external consultants. j). Initiating quality training for staff. k). Communicate the message of quality. l). Measuring quality costs. m). Apply quality tools and techniques through developing effective work groups. n). Evaluate the program at regular intervals.